Investigating the relation between heavy ion double charge exchange nuclear reactions and double beta decays. (December 2020) - Bellone, J I; Burrello, S; Colonna, M; Lay, J A; Lenske, H
Abstract: Heavy ion double charge exchange reactions (DCE) are discussed, within DWBA, in synergy with the main goal of the NUMEN project, i. e. to extract information on the 0νββ decay nuclear matrix element from DCE cross section measurements. The first step to reach this goal is to assess the analogy between the DCE nuclear matrix element and that describing 0νββ decay; then it is necessary to single out a term related to the desired double beta decay nuclear matrix element from the DCE cross-section expression (cross section factorization). Heavy ion DCE processes, are depicted in terms of sequence of two correlated or uncorrelated Single Charge Exchange (SCE) reactions, resembling in this way 0νββ and 2νββ decay, respectively. Here, the formalism for describing DCE reactions within the latter scenario is described. Once provided the formalism leading both to SCE and DCE cross section factorization, together with its limitations, a preliminary comparison with experimental DCE data is shown.